Begonia austrovietnamica (sect. Alicida, Begoniaceae), a handsome new species from South Vietnam - Peng, Ching-I; Truong, Nguyen-Dong; Nguyen, Danh-Duc; Lin, Che-Wei (Phytotaxa, 2018)
Begonia austrovietnamica C.-I Peng, C.W. Lin, D.D. Nguyen & N.D. Truong, a new species from Binh Thuan provice, southern Vietnam, is hereby described and illustrated. B. austrovietnamica resembles B. alicida C.B. Clarke in being a tuberous species with a dormant period, having 4-tepaled staminate flowers and 3-locular ovaries. However, the new species differs from B. alicida in being stemless with basal leaves (vs. erect stem), strongly asymmetrical (vs. slightly asymmetrical) lamina, inflorescence axillary (vs. terminal), pistillate flowers 6-tepaled (vs. 5-tepaled), ovary narrowly trigonous-ellipsoid (vs. trigonous-spheroid).